Psicologia do esporte: produção científica em Programas de Pós-Graduação em Educação Física e Psicologia de Minas Gerais (1980-2012) - Emmi Myotin (2018)
The aim of this study was to analise the scientific production in Sports Psychology (SP), in Minas Gerais (MG), investigating post-graduate programs (PGP) in Psychology (PSY) and Physical Education (PE), recommended by the Coordination of Improvement of Higher Education Personnel - CAPES, that presented theses and dissertations on themes related to SP, between 1980 and 2012. The purpose of this analysis was to support debates in the fields of PSY and PE, specifically the SP, about what and how to research, contributing to the decision-making on scientific policies in the area, setting priorities in the PGPs in PSY and PE. To achieve this goal, a descriptive, bibliographical research was carried out and it was characterized as a research called metascience. The researches were analysed according to the techniques of content analysis of Bardin (1977) and data presented in terms of frequency of the following categories analysed: PGPs and the institutions in which they were allocated; dissertations and theses, their respective authors and supervisors, thematic and theoretical approaches of PSY adopted in the researches, types of subject of the research, areas of educational background and gender of authors and supervisors and year of the submission. This survey indicated that MGinstitutions produced fifty-five dissertations on SP in the period between 1980 and 2012. Six institutions had PGP in PSY, but only the Universidade Federal de Uberlândia program presented dissertations with themes on SP (5% of the total production). In relation to PE programs, three institutions had PGPs - Universidade Federal de Minas Gerais and Universidade Federal de Juiz de Fora/Universidade Federal de Viçosa had programs presenting fifty-two dissertations with themes on SP (95% of the total production). With regard to the authors, the data demonstrated that, in the education background category, 70% had PE training; 9% training in PSY; 9% Physiotherapy training; 8% with double educational formation and 4% with unidentified educational background; in the gender category, 67% were male and 33% female. In summary, there was dominance of PE educational background and male dominance. In relation to the supervisors, the results indicated that, in the education background category, 67% were from the PE area and 33% from the PSY area; in the gender category, 67% were male and 33% female. There was, therefore, PE and male dominance. The types of subjects in the studies, 71% were athletes, 25% were coaches, 2% were referees and 2% were others. The topics covered were distributed as follows: analysis of psychological stress (25%); Leadership of the coach (9%); Quality of life of the athlete (7%); Expert performance of the athlete (7%); Expert coach performance (7%); Athlete career (5%); Motivation (5%); Mental training (5%) and others. The most used approaches were cognitive-behavioural (96%), psychoanalytic (2%) and psychosocial (2%). The results were discussed in the light of historical developments of the national and international SP and Pierre Bourdieu's Field Theory (1983). It was concluded that actions should be directed to promote the growth and development of SP, in Minas Gerais: (1) to offer a line of research in SP, especially in PGPs in the area of PSY, in a joint project of various programs; (2) to include the discipline SP in Psychology degree courses; and (3) to study the possibility of creating a specialization course in SP; and (4) to analyse the profession of PSY as a woman profession and its relation to sport and pshycal activities.